Reflection of learning styles on students' anxiety and learning levels in simulation education: An obstetrics and neonatology nursing experience - Kan Öntürk, Zehra; Kanığ, Merve; Aslan, Ergül; Kuğuoğlu, Sema (Istanbul University, 2021)
AIM: This study aimed to investigate whether the learning styles of nursing students affected their anxiety and learning levels during simulation education. METHOD: This was a cross-sectional and quasi-experimental study, which included a total of 60 nursing students. The students received simulation education about labor management and first care of newborns. The Learning Styles Inventory III, the Trait Anxiety Scale, and a pretest were used before the simulation education, and the Perceived Learning Scale and a posttest were used after the simulation education to collect data. RESULTS: According to data from the learning styles inventory, 81.6% of the students had a diverging learning style, 11.7% had an assimilating learning style, and 6.7% had an accommodating learning style. The mean state anxiety score was 49.83 +/- 10.59 just before the simulation. The mean pretest score was 51.50 +/- 16.96 and the mean posttest score was 54.17 +/- 15.22. The perceived learning score was 35.45 +/- 5.12. There was a significant difference in anxiety levels in terms of learning styles (p<.005). CONCLUSION: Most of the students in this study had a diverging learning style. Their anxiety levels did not change depending on their learning styles. The pretest/posttest results and perceived learning levels showed that simulation helped to achieve learning in all types of learners.
Keywords: Anxiety; Learning; Neonatology; Obstetrics; Simulation Training